Academic performance of 9th graders on Spatial Geometry: impact of personal and contextual variables - Brito, Luciana Pereira de (2021)
This article presents and discusses results from a study investigating the quality of Spatial Geometry academic performance of 9th grade students when they are about to be exposed to more complex concepts, geometric solids, and related problems in curricular learning experiences. Participants were Portuguese public school students. We also collected information about previous mathematics grades and mother’s schooling. A geometry test, a causal attribution to a school achievement test, and two reasoning tests – spatial and mechanical – were applied, and all collected data was statistically analysed and interpreted. To address the different nature of variables, we conducted a hierarchical linear regression. Results suggest that nearly 41% of variance on Spatial Geometry academic performance can be explained by the personal and contextual variables studied. The recommendation to schoolteachers involves designing learning experiences that engage students in spatial reasoning and high-order thinking skills.